A study of factors influencing rate of gain, quantity of feed consumed, and carcass grade. - Bell, F.W.; Mackintosh, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
Rate of gain in the feedlot is one of the most important factors determining the profits from cattle feeding. Also cattle which gain faster usually have more finish and sell for a higher price per hundredweight. There is considerable variation in rate of gain by different cattle in the same feedlot, and we need to know if the factors which cause these differences can be determined when the feeder cattle are selected.
Keywords: Beef; Carcass grade; Rate of gain; Feedlot